A Multimodal Approach to Challenging Gender Stereotypes in Children's Picture Books - Moya- Guijarro, A. Jesús; Ventola, Eija (Taylor & Francis, 2022)
A Multimodal Approach to Challenging Gender Stereotypes in Children's Picture Books is a collection of research papers in the fields of multimodality and picture books. 1 The chapters broaden the previous analyses of this genre, carried out from content, psychological, literary and didactic points of view.